(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article analyzes dialectal words, morphological, lexical, and phonetic features specific to the Tashkent dialect in Murad Mansur’s novel " The land of judaism ". In addition, the effective use of the Tashkent dialect and children’s speech words in the literary work is described.